Northrop Frye’s Approach to Symbolism in Jonathan Safran Foer’s Everything is Illuminated - Mohammed, Zhino Jabbar (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
This paper is a study of symbolism in Jonathan Safran Foer’s Everything is Illuminated (2002). The study aims to investigate the nature of symbolism through Herman Northrop Frye’s theory of literary symbolism within a postmodern background. The study is significant in both fields of postmodern literature as a framework and the Holocaust literature collectively. Theoretically, Frye’s theory of symbols is applied to Foer’s novel that is a literary masterpiece about the mass genocide of the European Jews, i.e. the Holocaust. The study will answer the following questions: What is Frye’s theoretical approach to literary symbolism? What is the impact of symbolism on Foer’s Everything is Illuminated? What are the specific symbols used in the novel? What is their significance and what do they stand for according to Frye’s theory? How does the writer contribute to them within the context of the novel? How do the symbols relate to themselves and outside world according to Frye’s theory? The findings of this study would be beneficial and valuable for students and researchers of the literary studies about symbolism, the Holocaust literature, English literature and postmodern American novels.